A study on Biosorptive Removal of Cd from Wastewater using Chironomid Larvae (Diptera: Chironomidae) - Bae, Yeon Jae; Ryoo, Keon Sang; Cho, Kijong; Baek, Min Jeong (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Cadmium (Cd) has caused serious public health problem due to its toxic nature. It is necessary to find a cost-effective method to dispose of wastewater containing Cd. Chironomid larvae as an alternative to conventional adsorbents were applied to remove Cd from wastewater. The sorption studies of Cd were carried out using laboratory-reared Glyptotendipes tokunagai (Diptera: Chironomidae) larvae. Kinetic and sorption capacity of chironomid larvae for Cd were determined by means of controlled experiments in a batch system. It was observed that removal efficiency of Cd was largely concentration dependent and more effective in lower concentration. At equilibrium, Cd was removed up to roughly 53 %. The sorption kinetics were found to conform to the pseudo-first-order kinetic model with a good correlation. Equilibrium sorption data were best fitted to the both Freundlich and Langmuir isotherm models owing to their correlation coefficient R2 values greater than 0.99. Considering the values obtained from isotherm constants 1/n and r, it is confirmed that Cd is sorbed favorably by chironomid larvae. With its relatively high removal capability for Cd, Chironomid larvae have enormous potential for application in wastewater treatment technologies.Â